INNOVATION OF POPULATION ADMINISTRATION SERVICES AT THE CITY OF CIREBON POPULATION AND CIVIL REGISTRATION SERVICE - Ratna Malinda, Liyana; Amelia, Gina; Taufik Hidayat, Moh; Heryanto, Yanto (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This research investigates the use of innovative civil registration services to improve government efficiency and citizen satisfaction. This innovation is realized through the implementation of innovative service approaches, revised procedures, improved service offerings, and new concepts. The aspects of efficiency, effectiveness and quality of population administration results are all enhanced by authentic development results. As an easily observable main indicator of government success, it emphasizes public services. The success of service innovation has the potential to improve the government's reputation in society. Qualitative methods with a descriptive orientation were implemented in this research. Comprehensive literature evaluation and data collection from online publications were used to obtain data. Indonesia has achieved great success in implementing service innovation, which has generated real benefits for society. Processing important documents, including identity cards (KTP), birth certificates and family cards, is now easier for individuals. Continuous refinement and development of service innovation is very important to create highly successful, highly efficient, and high-quality population administration services.